Audit of extracapsular cataract extraction and posterior chamber lens implantation as a routine treatment for age related cataract in east Africa. Issue 8 (1st August 1999) - Yorston, David; Foster, Allen
Abstract : AIMS: To evaluate the outcome of extracapsular cataract extraction (ECCE) and posterior chamber intraocular lens implantation (PC-IOL) in an African eye clinic during the transition from intracapsular cataract extraction to ECCE and PC-IOL. METHODS: A retrospective survey of 461 consecutive operations for age related cataract with a mean follow up of 52.9 weeks (range 0–275) and a minimum follow up of 4 weeks in 87.9% of eyes. RESULTS: A best corrected vision of 6/18 or better was obtained in 94.3% of eyes, and an uncorrected vision of 6/18 or better in 78.2% of eyes. Six eyes (1.5%) had a best corrected vision of less than 6/60. The visual acuity at 2 months was strongly predictive of the vision at 1 year or more after surgery. Preoperative biometry and IOL power calculation increased the proportion of eyes obtaining an uncorrected vision of 6/18 or better from 73.8% to 81.3%. Four eyes developed visually significant posterior capsule opacity. CONCLUSION: ECCE and PC-IOL can give very good results in an African setting. A better visual outcome should lead to increased demand for cataract surgery, which will eventually reduce the number of cataract blind people in Africa.